Digital Twin for Dynamic Construction Site Monitoring and Control - Mazlan, Elis Mardzianah; Mohd. Sarman, Asmawan; Ramzi, Al Sharif; Kamaruddin, Siti Syariazulfa; Abu Bakar, Ruzanah (Journal of Technology Management and Business, 2025)
The construction industry is inherently complex and poses significant safety challenges, requiring innovative solutions to enhance operational efficiency and risk management. Digital Twin (DT) technology has emerged as a transformative tool, offering real-time digital representations of physical construction sites to facilitate proactive decision-making and improve site monitoring. This study aims to explore the integration of Digital Twin technology into construction site management, focusing on its impact on safety, operational efficiency, and risk mitigation. By leveraging real-time data, predictive analytics, and Internet of Things (IoT) sensors, the research seeks to assess the effectiveness of DT in enhancing safety protocols and streamlining construction workflows. A mixed-methods approach was adopted, combining quantitative surveys with construction managers and safety officers, along with qualitative interviews with industry professionals. Statistical analysis was conducted to evaluate the correlation between DT adoption and safety performance indicators, while thematic analysis provided insights into practical challenges and benefits. Findings indicate a significant reduction in workplace accidents and near-miss incidents, with a 35% decrease in reported accidents following DT implementation. Additionally, participants highlighted improved situational awareness, proactive risk management, and a cultural shift towards safety-conscious practices. However, challenges such as initial costs and training requirements were identified as key barriers to widespread adoption. The study underscores the potential of Digital Twin technology to revolutionize construction site management by enhancing safety outcomes and optimizing operational efficiency. These findings offer valuable insights for industry practitioners, policymakers, and researchers, advocating for increased investment in DT systems to promote safer and more sustainable construction environments.